A novel variation in DEPDC5 causing familial focal epilepsy with variable foci - Wang, Yanchi; Niu, Wenbin; Shi, Hao; Bao, Xiao; Liu, Yidong; Lu, Manman; Sun, Yingpu (Frontiers in Genetics, 2024)
Background Disheveled, EGL-10, and pleckstrin (DEP) domain-containing protein 5 (DEPDC5) is a component of GTPase-activating protein (GAP) activity toward the RAG complex 1 (GATOR1) protein, which is an inhibitor of the amino acid-sensing branch of the mammalian target of rapamycin complex 1 (mTORC1) pathway. GATOR1 complex variations were reported to correlate with familial focal epilepsy with variable foci (FFEVF). With the wide application of whole exome sequencing (WES), more and more variations in DEPDC5 were uncovered in FFEVF families. Methods A family with a proband diagnosed with familial focal epilepsy with variable foci (FFEVF) was involved in this study. Whole exome sequencing (WES) was performed in the proband, and Sanger sequencing was used to confirm the variation carrying status of the family members. Mini-gene splicing assay was performed to validate the effect on the alternative splicing of the variation. Results A novel variant, c.1217 + 2T>A, in DEPDC5 was identified by WES in the proband. This splicing variant that occurred at the 5′ end of intron 17 was confirmed by mini-gene splicing assays, which impacted alternative splicing and led to the inclusion of an intron fragment. The analysis of the transcribed mRNA sequence indicates that the translation of the protein is terminated prematurely, which is very likely to result in the loss of function of the protein and lead to the occurrence of FFEVF. Conclusion The results suggest that c.1217 + 2T>A variations in DEPDC5 might be the genetic etiology for FFEVF in this pedigree. This finding expands the genotype spectrum of FFEVF and provides new etiological information for FFEVF.